Repeated injection of multivitamins and multiminerals during the transition period enhances immune response by suppressing inflammation and oxidative stress in cows and their calves - Somagond, Yallappa M.; Alhussien, Mohanned Naif; Dang, Ajay Kumar (Frontiers in Immunology, 2023)
Periparturient dairy cows undergo major physiological and metabolic changes as well as immunosuppression, associated with decrease in plasma concentrations of various minerals and vitamins. The present study was conducted to investigate effects of repeated injections of vitamins and minerals on oxidative stress, innate and adaptive immune response in periparturient dairy cows and their offspring. Experiment was carried out on 24 peripartum Karan-Fries cows, randomly divided into four groups (n=6): control, Multi-mineral (MM), Multi-vitamin (MV) and Multi-minerals and Multi-vitamin (MMMV). Five ml of MM (Zinc 40 mg/ml, Manganese 10 mg/ml, Copper 15 mg/ml, Selenium 5 mg/ml) and five ml of MV (Vitamin E 5 mg/ml, Vitamin A 1000 IU/ml, B-Complex 5 mg/ml, and Vitamin D3 500 IU/ml) were injected intramuscularly (IM) to the MM and MV groups. MMMV group cows were injected with both. In all treatment groups, injections and blood sampling were carried out on 30th, 15th, 7th days before and after expected date of parturition and at calving. In calves, blood was collected at calving and on 1, 2, 3, 4, 7, 8, 15, 30 and 45 days post-calving. Colostrum/milk were collected at calving and at days 2, 4, and 8 post-calving. A lower percentage of total neutrophils and immature neutrophils, higher percentage of lymphocytes together with increased phagocytic activity of neutrophils and proliferative capacity of lymphocytes found in blood of MMMV cows/calves. Lower relative mRNA expression of TLRs and CXCRs and higher mRNA expression of GR-α, CD62L, CD11b, CD25 and CD44 found in blood neutrophils of MMMV groups. Total antioxidant capacity was higher, activity of antioxidant enzymes (SOD and CAT), TBARS levels were lower in the blood plasma of treated cows/calves. In both cows/calves, plasma pro-inflammatory cytokines (IL-1α, IL-1β, IL-6, IL-8, IL-17A, IFN-γ and TNF-α) increased, whereas anti-inflammatory cytokines (IL-4 and IL-10) decreased in MMMV groups. Total immunoglobulins increased in colostrum/milk of MMMV injected cows and plasma of their calves. Results indicate that repeated injections of multivitamins and multiminerals to peripartum dairy cows could be a major strategy to improve immune response and decrease in inflammation and oxidative stress in transition dairy cows and their calves.